Software design methodology - Zhu, Hong, 1961- (Elsevier Butterworth-Heinemann, 2005)
Software design methodology has come a long way since the 1960s and 1970s when programmers were limited to Pascal/C and SA/SD to create systems. When creating information systems for today's world, many factors must be taken into consideration including globalization, the software lifecycle, modeling, coding, testing, and maintenance. * In depth coverage of large scale software systems and the handling of their design problems * Many worked examples, exercises and case studies to reinforce theory and practice * Gain an understanding of the general theory of design methodology.